154 Post-Phalloplasty Urinary Function Test: A Novel Outcome Instrument to Capture Urinary Dysfunction and Quality of Life after Phalloplasty. Issue 1 (1st April 2022) - Liu, J.; Eisenbeis, L.; Preston, S.; Burnett, A.; DiCarlo, H.; O'Brien Coon, D.
ABSTRACT: Introduction: Due to rapidly growing demand for gender affirmation surgery, the number of phalloplasties performed has increased dramatically. Existing research focuses largely on surgical complications and in transmen there is no widely accepted post phalloplasty specific urinary questionnaire. Objective: The objective of this study is to present a novel patient-reported outcome instrument – the Post-Phalloplasty Urinary Function Test (PPUFT) – and protocol to measure post-void urethral volume (PVUR) and preliminary results. Methods: We conducted a cross-sectional pilot study in a cohort of 15 adult transmen who had undergone phalloplasty with urethral lengthening surgery between 2018 and 2021 by a single center. Patients had stable urinary function via the neophallus at time of survey. Patients filled out the PPUFT and were asked to record their PVUR as per our protocol. Results: The average PPUFT score was 8.86 out of 40 and the average quality of life (QOL) score was 2.6. Post void dribbling constituted the major complaint and on average comprised 63% of the reported PPUFT score. Average PVUR was 2.16 ml (range 0.5-5.6 ml). There was a positive correlation between higher PPUFT and worse reported quality of life (p=0.01; R2=0.39). Conclusions: Current questionnaires accepted in cis-male urology have limitations for accurately capturing urinary dysfunction in this specific patient group, especially post-void symptoms from the unique anatomy of a flap-based neo-urethra. The combination of PPUFT and PVUR measurement offers potential for quantifying urinary function and quality of life in patients who undergo phalloplasty. Future studies will validate these instruments. Disclosure: No